Studies of Migration in Ecuador: From National Development to Mobilities - Eguiguren, María Mercedes (2017)
The article presents a review of the studies on migration in Ecuador during the period 1960-2016. It addresses the main debates that have marked these studies, the contexts of academic production, and the way in which migrations and their social and economic conditions have influenced the constitution and orientations of the field. Three stages go through the academic production: a first one where the internal migrations are approached from a spatial phenomena analysis; a second that deals with the links between agricultural transformations and migration; and a third that shows a transition from a resurgence of migration in the literature to recent studies on the diversification of mobilities in the country.